Laparoscopic treatment of ureteropelvic junction obstruction in five pediatric cases of pelvic kidneys. Issue 6 (December 2015) - Muller, Cécile O.; Blanc, Thomas; Peycelon, Matthieu; El Ghoneimi, Alaa
Summary: Objective: Ectopic kidney is a rare urologic condition and may be revealed by ureteropelvic junction obstruction (UPJO) in children, with pelvic kidney being the most common location. Our experience using a minimally invasive approach to treat UPJO by dismembered pyeloplasty led us to report five cases of UPJO with pelvic kidney operated on by transperitoneal laparoscopy, focusing on medium-term follow-up results and surgical technique. Patients and methods: From 1999 to 2010, we reviewed all cases of UPJO managed in our center, a total of 391 patients. Among those, 125 patients were operated on via a minimal invasive approach, 104 by retroperitoneoscopy, and 21 by transperitoneal laparoscopy. Five patients presented ectopic pelvic kidney and were retrospectively reviewed. US-scan and uro-MRI were done preoperatively in all cases for anatomic and functional evaluation. Peri-operative data such as operative time, transfusion, and complications were reported. At last clinic, sonographic and functional evaluation was noted. Focusing on surgical technique, we reported the tips and tricks to successfully and easily perform the dismembered pyeloplasty: optimization of the trocars' location according to the kidney location and use of a transparietal stay stitch to stabilize the suture line of the pyeloplasty. Results: All five patients underwent dismembered pyeloplasty, at a mean age of 8 years and a mean weight of 23.4 kg. Mean operative time was 213 min (min–max: 180–245). One case of giant hydronephrosis and megacalicosis required conversion at the beginning of the learning curve. None of the patients required blood transfusion. Mean hospital stay was 2.4 days (range: 1–4). All the patients had an uneventful postoperative recovery and good postoperative functional results, with either stable or improved pelvic dilatation and renal function at a mean follow-up of 3.3 years (range: 2–5.6). Discussion: This small series of five ectopic kidneys reflects the surgical challenge for the pediatric surgeon to perform reconstructive surgery on an abnormal anatomy. However, increasing experience in robotics in urologic pediatric surgery may lead to shortening of operative time and facilitate both dissection and suturing. Conclusion: Dismembered pyeloplasty by transperitoneal laparoscopy is a feasible although technically demanding, safe and effective approach in the management of ureteropelvic junction obstruction in pelvic kidney in children.